2019
DOI: 10.1002/adom.201901202
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion‐Engineering‐Enabled “Sketch and Peel” Lithography for Aluminum Plasmonic Nanogaps

Abstract: in the near field and amplify both linear and nonlinear phenomena at the singlemolecule and single-particle level. [5][6][7][8][9] Choosing an appropriate plasmonic material is significant for different plasmonic applications, usually considering the cost, performance, and process compatibility. Among these materials, silver (Ag) is favored due to its low loss, which supports a strong plasmon resonance in the visible and near-infrared regions. [10] However, the oxidization of Ag in air greatly changes its opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…101 Furthermore, by introducing a self-assembled monolayer to engineer the surface energy of the substrate, the adhesiveness of the Al film outside outline template is significantly decreased to implement the selective peeling process, various plasmonics Al nanostructures with sub-20 nm feature sizes were successfully achieved by SPL approach, suggesting the tremendous potential and fabricating ability of the technology. [102][103][104] To optical properties and applications of artificial plasmonic metal atoms, the hybridization model for the plasmon response of complex nanostructures provides a simple effective guideline. 105 As shown in Fig.…”
Section: Figure 4 the Schematic Illustration Of General Growth Models Of Metal Filmsmentioning
confidence: 99%
“…101 Furthermore, by introducing a self-assembled monolayer to engineer the surface energy of the substrate, the adhesiveness of the Al film outside outline template is significantly decreased to implement the selective peeling process, various plasmonics Al nanostructures with sub-20 nm feature sizes were successfully achieved by SPL approach, suggesting the tremendous potential and fabricating ability of the technology. [102][103][104] To optical properties and applications of artificial plasmonic metal atoms, the hybridization model for the plasmon response of complex nanostructures provides a simple effective guideline. 105 As shown in Fig.…”
Section: Figure 4 the Schematic Illustration Of General Growth Models Of Metal Filmsmentioning
confidence: 99%
“…[143] A number of variations to the SPL procedure have been reported. [144][145][146][147][148] For instance, instead of using a negative resist, it is possible to directly create nano-trenches in a deposited metal film by FIB milling before selectively removing the metal outside of the trenches by peeling, see Figure 14. [142] In the case of a silicon substrate, it has been shown that slight over-milling of the unwanted metal causes a thin layer of silicon atoms to be sputtered onto the side walls of the retained metal, which serves to protect the retained metal from damage during the subsequent peeling step.…”
Section: Peeling-based Methodsmentioning
confidence: 99%
“…SPL has also been extended to strongly adhesive metals such as aluminum by depositing a fluorine‐based self‐assembled monolayer on top of the substrate to modify its surface energy. [ 145 ] All in all, SPL is a versatile and reliable method for nanogap patterning that provides a good balance between speed and throughput as it requires only the outline of the patterns to be defined in the photoresist. However, it is best suited to weakly adhesive metals such as gold and silver or substrates treated with adhesion‐reducing surface modifiers, which may potentially compromise the mechanical stability of the resultant nanostructures.…”
Section: Alternative and Emerging Approachesmentioning
confidence: 99%
“…However, the limitations of those existing fabrication techniques make it difficult to fabricate three-dimensional (3D) metamaterials [ 9 , 10 ]. Therefore, the two-dimensional (2D) metamaterials, metasurfaces, have been rapidly developed and applied owing to their relatively easy fabrication methods and technologies [ 11 , 12 , 13 , 14 , 15 , 16 ]. Moreover, metasurfaces can control the amplitude [ 17 , 18 , 19 , 20 ], phase [ 21 , 22 , 23 , 24 ], and polarization [ 25 , 26 , 27 , 28 ] of electromagnetic waves, leading to a fact that various applications based on their unique properties have been developed, such as metalens focusing [ 29 , 30 , 31 ], holographic imaging [ 32 ], vortex light modulation [ 33 ], and abnormal deflectors [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%